The Role of Shakespeare in Shaping the English Language (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article explores the significant role of William Shakespeare in shaping the English language. It examines his impact on vocabulary, idioms, grammar, poetic form, and literary expression. The article also discusses Shakespeare's influence on cultural references, global translation, and his enduring legacy as a linguistic innovator.